(untitled) (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
A new Geographical Information System (GIS) approach is proposed to assess primary potential hydropower site, explicitly identifying highly possible hydropower locations spatially, over a large area in a short time. The results from this approach were validated with an existing hydropower site in the Bhote Koshi catchment in Nepal. Altogether 885 number of searches made along the river streams each covered a circular area of radius 10 km, with distance between headwork and power houses of 500 m intervals, thus, identified 297 highly potential sites out of total 2655 during evaluation. The results indicate that, 52 sub-catchments have potential areas and seven specific hydropower locations overlapped with existing hydropower projects. This approach is suitable for initial screening only and the produced results significantly facilitate further in-depth feasibility study to engineering and economic analysis for hydropower potential of the basin. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 23 Year: 2018